Moisture Sensitivity of Hot Mix Asphalt Modified with Micronized Calcium Carbonate - Hamedi, Gholam Hossein; Nejad, Fereidoon Moghadas (Periodica Polytechnica Civil Engineering, 2024)
Moisture sensitivity in an HMA refers to the loss of mastic cohesion and durability between the bitumen and aggregates due to water presence. Various methods exist to mitigate this type of sensitivity, with one of the most important approaches being the incorporation of anti-stripping agents into either the bitumen or aggregate materials. Based on this premise, the current study investigates the impact of using micronized calcium carbonate powder (MCCP or CaCo3) as a modifier for bitumen on moisture sensitivity in HMA. Three types of aggregates with different mineralogical properties (limestone, granite, and quartzite), and PG 64–16 bitumen (along with 2% and 4% MCCP based on the mass of the bitumen) were utilized. The modified Lottman test was performed under 1 to 5 freeze-thaw cycles while measuring surface free energy (SFE) elements for both bitumens and aggregates with Wilhelmy Plate (WP) and Universal Sorption Device (USD), respectively. The results of the moisture sensitivity test on the asphalt mixtures used in this study demonstrate that the addition of MCCP in the modified samples has led to a reduction in the sensitivity of the asphalt mixtures, particularly in multiple freeze-thaw cycles, compared to the control samples. Furthermore, findings from SFE analysis demonstrated that MCCP enhanced cohesion free energy (CFE) which subsequently reduced rupture probability within the bitumen membrane. Additionally, it improved adhesion between acidic aggregates susceptible to moisture-induced sensitivity and bitumens.